Gambaran Pasien Reumatoid Artritis di RSUD Arifin Achmad Riau Province 2015 - 2019 - Jelita Sri Agustin; Huriatul Masdar; Asrizal Asrizal (Fakultas Kedokteran Universitas Riau, 2020)
Rheumatoid Arthritis (RA) is a chronic autoimmune disease that causes tissue damage, deformity, and death if not treated immediately. The aim of this study to description of RA patients in the Regional General Hospital (RSUD) Arifin Achmad Riau Province 2015 – 2019. The results showed that total cases was 55 cases with the more common in female (87,3%) with most age group was 46-55 years (34,5%) and the main complaints were joint pain (85,5%). Rheumatoid arthritis patients with laboratory examinations were non-reactive rheumatoid factor (RF) levels by 20 patients out of 30 patients, levels of Anti-Citrullinated Protei Antibodies (ACPA) or Immunoglobulin G anti-Cyclic Citrulinated Protein (IgG anti-CCP) reactive by 3 patients out of 4 patients, levels C-Reactive Protein (CRP) abnormal by 18 patients out of 21 patients and levels Erythrocyte Sedimentation Rate (ESR) abnormal by 20 patients out of 23 patients. The results also showed that the most pharmacological therapy given was corticosteroid (87,3%)